Powieść Popiół i diament Jerzego Andrzejewskiego a cenzura w NRD - Rajch, Marek (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The article presents how the Polish novel Popi.ł i diament (Ashes and Diamonds) by Jerzy Andrzejewski was received by censors in the German Democratic Republic. The novel was first published in East Germany in the 1960s, although attempts to release it were made as early as sixteen years earlier. The author of the article recalls the reviews by German censors who refused to give consent to the novel’s publication on the East German market and whose decisions were affected not by the content of the book alone, but also by the social and political situation in both the Polish People’s Republic and the German Democratic Republic.